"SILVER ECONOMY": SOCIAL ASPECTS AND SUSTAINABLE DEVELOPMENT - Kuzheliev , M.O.; Fedyna , V.V.; Stabias , S.M. (The actual problems of regional economy development, 2021)
The article is devoted to the study of the essence of the concept of "silver economy" as a new approach to solving the problem of population aging, which is faced by both the world and Ukraine. The methodology of the study were the methods of factor analysis and synthesis, dialectical, logical-semantic, graphic, methods of comparison and generalization. Traditionally, an aging population is perceived as a financial burden on the economy and a threat to the well-being of future generations. In difficult demographic conditions, the developed countries of the world have begun to implement special policies aimed at supporting the aging population. The UN principles on the elderly are considered, the main thesis of which is to create conditions for maximum self-realization in society, to prevent age discrimination, which together will ensure a decent life for elderly Ukrainians. It is proved that the aging of the population, in addition to the negative consequences, can become a new resource for economic growth of the country by expanding the labor market, increasing consumption and increasing production. Important economic, socio-cultural and political-legal factors of formation and development of the "silver economy" are considered. It is noted that such a process should take place within the framework of state regulation. Accordingly, the main directions of state policy that will promote the development of the "silver economy" in the country are outlined. The influence of the "silver economy" on the efficiency of the development of the pension system in the country has been established. It is determined that the pension reform is a method of protecting the sustainability of the pension system by increasing the employment rate of the elderly. It has been proven that in the context of pension reform, "silver age" people have a hidden potential to solve the financial problems of the pension system and can be a source of balancing such a system. It is concluded that the positive impact of the "silver economy" is possible only if modern society is aware of the need to change attitudes towards the elderly and their full integration into the social and economic life of society.